(untitled) (Research, Society and Development, 2019)
It aimed to develop cereal bar with added carrots and beets. Were processed by mixing, heating and compression. The vegetables added ranged from 0% to 100%. Five formulations were prepared and evaluated for physical and chemical characteristics and color parameters. We evaluated the sensory aspects only of formulations which obtained the best result in the color test (F2 and F5). The bars had high humidity (23%), ash (1.35%) Acidity (0.19 0.39%) total solids (74 78%), fat (6.08 to 11.08%), sodium content (15,39mg / 25g) and fiber (4,36 à 4,88% / 100g). The addition of vegetable favored the appearance of the color bar, however, high humidity detracted from their texture and crispness. However, the acceptability was satisfactory for the evaluated attributes. The carrots and beets increase provided distinctive flavor and increased the nutritional value of the bars, contributing to the development and increased consumption of vegetables by the population.